The Hemobag: the modern ultrafiltration system for patients undergoing cardiopulmonary by pass - Colli, Andrea (BioMed Central, 2012)
BACKGROUND: The return of extracorporeal circuit blood at the termination of cardiopulmonary bypass (CPB) is an important feature of blood conservation during cardiac surgery procedures globally. We report our initial clinical evaluation of the Hemobag system a blood-salvaging device designed for whole blood recovery of residual post-CPB volume. METHODS: Residual whole blood is hemoconcetrated through the multipass “recovery loop” circuit separate from the CPB and collected in the Hemobag System. This allows the surgeons to continue with surgery, decannulate, and administer protamine simultaneously while the Hemobag is in use and the CPB circuit remains safely primed. We have compared 25 patients receiving the Hemobag to a control group of 25 patients treated with the cell washer that represented our previous standard of care method of circuit blood-salvaging technique. RESULTS: The Hemobag system provided significantly higher hemoglobin, hematocrit, fibrinogen, albumin, and total protein levels in the final product reducing the amount of wasted autologous blood cells. There were no device-related complications. There were no significant differences in terms of blood utilization, chest tube drainage and clinical outcomes over the entire postoperative period among groups. CONCLUSIONS: These results suggest that the Hemobag system is a safe and efficient method to multipass hemoconcentrate the residual diluted blood of the CPB circuit. The Hemobag has demonstrated its ability to maximize the composition of the residual CPB volume to achieve the best possible post-CPB hemoglobin, plasma protein and coagulation factors profile for the patient respect to CW.